2001
DOI: 10.1007/s001250100560
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus antibody levels during the first two years of life in prediabetic autoantibody-positive children

Abstract: Aims/hypothesis. We evaluated the role of enterovirus infections in the pathogenesis of Type I (insulindependent) diabetes mellitus by monitoring enterovirus antibody levels in prediabetic children who turned positive for diabetes-associated autoantibodies in a prospective birth cohort study. Methods. Serial serum samples taken during prospective observation starting at birth were analysed for IgG and IgA class antibodies against enterovirus antigens including purified coxsackievirus B4, echovirus 11, poliovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Country was included as a stratification factor in the proportional hazards analyses. Additional covariates included in the model were first-degree relative [26], HLA [27], gender, ever breastfed [28, 29], probiotic use prior to 3 months of age [30], and eight different previously identified single nucleotide polymorphisms [31]. The primary variable of interest was cumulative ANAP use through 2.5 years of life as a time dependent covariate.…”
Section: Methodsmentioning
confidence: 99%
“…Country was included as a stratification factor in the proportional hazards analyses. Additional covariates included in the model were first-degree relative [26], HLA [27], gender, ever breastfed [28, 29], probiotic use prior to 3 months of age [30], and eight different previously identified single nucleotide polymorphisms [31]. The primary variable of interest was cumulative ANAP use through 2.5 years of life as a time dependent covariate.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in a recent study, Yeung and colleagues showed that children with islet autoimmunity have higher levels of multiple cytokines, consistent with an active inflammatory process in the prediabetic state, yet these findings were unrelated to coincident EV infection [15]. However, the DIPP study found a close temporal association between the appearance of the first diabetes-associated autoantibodies and EV infections [16,17], and similar results were seen in the TRIGR study [18]. …”
Section: Brief Historymentioning
confidence: 69%
“…Somewhat paradoxically, it has also been reported that induction of IFNs in virus-infected beta cells was critical for their survival during viral infection [18, 53]. Increased numbers of enteroviral infections have been reported in prediabetic individuals [2, 4, 54], and recently enteroviruses have been detected in pancreatic tissue from type 1 diabetic patients [6, 22, 23]. Taken together, these findings suggest that pancreatic viral infection may occur before and during onset of clinical diabetes, and that alterations of antiviral defense in virus-infected pancreatic beta cells may influence susceptibility to developing type I diabetes.…”
Section: Discussionmentioning
confidence: 99%